Effect of carbon-skeleton isomerism on the dielectric properties and proton conduction of organic cocrystal compounds assembled from 1, 2, 4, 5-benzenetetracarboxylic acid and piperazine derivatives. (21st June 2019) - Liang, Xiaoqiang; Chen, Yixiang; Wang, Li; Zhang, Feng; Fan, Zenglu; Cao, Tingting; Cao, Yaya; Zhu, Huifang; He, Xinyue; Deng, Bolin; You, Yazhi; Dong, Yu; et al.
Abstract : Two isostructural 2D supramolecular cocrystal compounds show different dielectric responses and proton conductivities due to the alteration of the carbon-skeleton of piperazine derivatives. Abstract : Multifunctional materials have rapidly attracted increasing attention owing to their novel, unpredictable, and unique properties, and potential applications in sensors, switches and smart materials. However, a lack of deeper understanding of performance optimization and structure–property relationships hampers the investigation of the coupling mechanism and further development of multifunctional materials. In this study, using the intrinsic merits of cocrystal materials and the strategy of molecular design, two isostructural 2D supramolecular cocrystal compounds [(H3 betc)(H-Hopip)0.5 ·(H2 O)] [OCC 1, H4 betc = 1, 2, 4, 5-benzenetetracarboxylic acid, Hopip = homopiperazine] and [(H3 betc)2 (H2 -Mepip)·(H2 O)] [OCC 2, Mepip = 2-methyl-piperazine] were successfully synthesized and further structurally characterized. OCC 1 and OCC 2 show different dielectric responses and proton conductivities due to the alteration of the carbon-skeleton of piperazine derivatives. Interestingly, a higher dielectric response (2480 at 100 Hz) and proton conductivity (3.65 × 10 −4 S cm −1 at 298 K and ∼97% RH) is observed in OCC 2, which was better than those of some reported cocrystals, metal–organic framework materials and organic covalent compounds. The mechanism of dielectric response was also clearly elucidated by means of temperature-dependent Raman spectroscopy measurements. More importantly, there is good correlation between macroscopic properties and microscopic structures in OCC 1 and OCC 2. Furthermore, OCC 1 and OCC 2 show high dielectric constants and moderate proton conductivities under ambient conditions, which satisfies the criteria as the dispersed phase of electrorheological fluids. The study will provide valuable insight into investigating structure–property relationships for crystal materials at the atomic level, and also lay the foundation for the study of electrorheological fluids of organic cocrystal compounds.